Sintesis dan Karakterisasi Bionano Hidroksiapatit (HAp) Secara Insitu Dengan Metode Hidrotermal - Laode A. Kadir; Dian Permana; Thamrin Azis (Cokroaminoto Journal of Chemical Science, 2022)
The pokea clamshell contains high calcium content which has the potency to be used as a precursor of calcium in synthesis of hydroxyapatite (HAp). This study aimed to utilize the waste of the pokea clamshells as a precursor of CaO in synthesizing of HAp, and to carry out the characterizations. Analysis of CaO content XRF showed that pokea clamshell after calcination was 94.23% (by weight). The hydrothermal method synthesized HAp confirmed the formation of single phase of HAp as indicated by the sharpness of the phosphate (PO43-) vibration peak at 561.85; 962.01; and 1024.55 cm-1.